Assessment of hazardous trace metals and associated health risk as affected by feed intake in buffalo milk - Samun Shahzad; Kamran Ashraf; Nusrat Ehsan; Khawar Sultan; Asim Abbasi; Sobia Tabassum; Amina Muzamil; Nazih Y. Rebouh; Qamar uz Zaman (Scientific Reports)
Abstract The presence of hazardous trace metals in the food chain poses a significant risk to human health. Milk is an essential part of a balanced dietary regimen, playing a crucial role in supporting optimal growth and development of the human body. However, the continuous consumption of metal-contaminated milk might potentially lead to the onset of chronic health disorders. The objective of this study was to investigate the fluctuation of physico-chemical attributes and concentrations of toxic trace metals in buffalo milk and examine their relationship with various feed types (alfalfa fodder, maize silage, and a combination of fodder and silage). Additionally, the study attempted to determine the potential health hazards that these levels may offer to consumers. The study revealed that the characteristics of the milk, such as its physical, chemical, and metallic properties, were affected by the type of feed. The measured physicochemical properties encompassed pH values ranging from 5.12 to 9.13, electrical conductivity values ranging from 995 to 1799 µS/cm, total solids content ranging from 10.12 to 15.9 mg/L, moisture content ranging from 84.5% to 90%, density ranging from 17.2 to 30.29 g/mL, and fat content ranging from 3.9% to 10.9%. The metal concentrations varied within the following ranges: lead (0.00229–0.029 mg/L), cadmium (0.00122–0.058 mg/L), mercury (0.00101–0.03 mg/L), and arsenic (0.0007–0.198 mg/L). Significant positive associations were found between the levels of metals and the types of feed. Principal component analysis identified the considerable influence of certain feed categories on the metal concentration found in the milk. While certain estimated daily intake (EDI) and health risk index (HRI) values surpassed suggested criteria, the hazard index (HI) values remained within safe ranges. This indicates that the total risk of metal ingestion through milk consumption is modest. It is crucial to continuously check the presence of both organic and inorganic pollutants in milk, and regulatory agencies should implement stringent procedures to prevent contamination.